La identificación de las unidades léxicas integrantes de las medioestructuras semánticas de los verbos - Mehlberg, Martin (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2004)
Most verbs exhibit a range of different conventionalized meanings (lexical units), which form the so-called mediostructure of the verb. Based on the model of Lexical Syntax (Subirais, 2001), we will outline a possible identification procedure for these various lexical units. This procedure consists in determining the class of linear projection and of syntactic redundancy to which the lexical unit in question belongs.
Identification of lexical units members of the semantic mediostructures of verbs